Pengembangan Bahan Ajar Biologi Berbasis Contextual Teaching Learning untuk Mengefektifkan Pembelajaran bagi Siswa SMA - Sukmawati, Fatma (FENOMENA, 2015)
The objectives of this study are: (1) to know the need of teaching materials for the senior high school teachers and the students, (2) to know the procedures of Biology teaching materials development of contextual teaching learning-based teaching, (3) to develop Biology teaching materials of contextual teaching learning-based teaching. The research method of this study is research and development. This study found: firstly, the need of teaching materials for the senior high school teachers and the students considers some elements, they are a) situational context, b) fits to curriculum, c) exercises/tasks enable to activate the studentsâ achievement, d) practical based implementation, and e) interesting, clear, and easy to understand. Secondly, the model of development is adapted from Borg and Gall, they are: data collection, planning, drafting a model, experimenting the model, revision the draft, field experiment, revising the final draft, and implementation. Thirdly, the score of post test shows 66.9 (control class) and 79.6 (experimental class), t-value of f value is 2.67 > 1.67 of f table. It can be concluded that the use of Biology CTL based-teaching materials enables to improve the studentsâ achievement in learning Biology.